(3GdLhgQ GdKejf aj SjQ Gdedhc hGdSdGWjfs - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf heG Jhajbi EdG HGddg gPG cJGH LeYJ ajg CNHGQ GdNdaGA GdQGTOjf hGdedhc hGdSdGWjf s
(3Cdag HGTGQI GdXGgQ HQbhbs
(3GfXQ GdbSe GdChd HQbe (B208 (3hGdbSe GdKGfi Qbe (B643s
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs